How does rock-ramp fishway surface texture affect the passage success of small-bodied Great Plains fishes? - Brittain, Cole, author; Myrick, Christopher A., advisor; Kanno, Yoichiro, committee member; Angeloni, Lisa, committee member (Colorado State University. Libraries, 2021)
The waterways of the North American Great Plains have experienced extensive fragmentation from instream structures and intermittency caused by excessive dewatering. The modifications to these waterways include numerous barriers that prevent the upstream movement of fish. State and federal resource management agencies have turned to fish passage structures to restore connectivity. However, the passage efficiency of current structures may be limited for native small-bodied fish species by a lack of information on how fish swimming behavior and performance are affected by the key fishway design parameters of slope, length, and texture. Recent research has provided more information on fishway slope and length, and identified texture of the surface between the larger roughness elements as an area needing more investigation. We evaluated the effects of four surface textures (smooth; 1 – 2 mm diameter coarse sand; 6 – 10 mm diameter pea gravel, and; 19 – 31 mm diameter small cobble) on the passage success of three native small-bodied fish species, Arkansas Darter (Etheostoma cragini), Flathead Chub (Platygobio gracilis), and Stonecat (Noturus flavus) using a 6.1-m long experimental rock ramp fishway set at a 6% slope. Our results demonstrated that passage success for the Arkansas Darter increased from 0% on the smooth substrate to 32.2% for the small cobble substrate. A similar pattern was observed for the Stonecats, with an increase in passage success from 31.1% on the smooth substrate to 86.7% on the small cobble substrate. Flathead Chub passage success was independent of substrate treatment and exceeded 90% in all cases. Our study suggests that the use of more highly textured substrates is a viable option for increasing the passage success of small-bodied fishes that otherwise do not perform well on rock ramp fishways.